72.3k views
1 vote
If x+y=5 and xy=3

√(x ) + √(y = )


User Nicktones
by
5.1k points

1 Answer

2 votes

Notice that if both
x,y are positive, then


xy = 3 \implies √(xy) = \sqrt x \sqrt y = \sqrt3

We also have the binomial expansion


x + 2√(x)√(y) + y = \left(\sqrt x\right)^2 + 2 \sqrt x \sqrt y + \left(\sqrt y\right)^2 = \left(\sqrt x + \sqrt y\right)^2

Then


\left(\sqrt x + \sqrt y\right)^2 = (x + y) + 2√(xy) = 5 + 2\sqrt3 \\\\ \implies \sqrt x + \sqrt y = \boxed{√(5 + 2\sqrt3)}

Let's see if we can denest the radical. Suppose we could write


√(5 + 2\sqrt3) = a + b \sqrt c

for some non-zero integer constants
a,b,c (and
c>0). Squaring both sides gives


5 + 2\sqrt3 = a^2 + 2ab\sqrt c + b^2c

Let
c=3 and
ab=1. Then
a^2 + b^2c = 5, which gives


a^2 + 3b^2 = 5


a^2 + \frac3{a^2} = 5


a^4 - 5a^2 + 3 = 0

We can solve this with the quadratic formula. However, it'll lead to non-integer solutions for
a,b, so we cannot denest after all.

User Klumsy
by
5.1k points